Quick appraisal monitoring and evaluation tool for the Local Technical Agroclimatic Committees (LTACs) in Latin America (LAM) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The instrument has been developed and has been successfully tested in LTACs in Guatemala in 2020, with a sample of more than 200 people. A working paper summarizes the results of the pilot test and the tool is ready to use at the LAM level in the 41 LTACs.